Self-pollination in Mirabilis longiflora L. (Nyctaginaceae) - Hernández, Héctor M. (Instituto de Ecología, A.C., 1990)
Mirabilis longiflora displays a combination of reproductive characters associated with pollination by sphingids. However, in a population from the State of Michoacán the species appears to strongly depend on autogamy. Controlled pollinations revealed that individuals are self-compatible, and have a high potential for autogamy. In addition, the observations showed an apparent absence of flower visitors.